An Inventory Model for Deteriorated Item with Time- and Inventory-dependent Demand and Backorder - Dharma Lesmono; Taufik Limansyah; Ignatius A. Sandy (LPPM Institut Teknologi Sepuluh Nopember, 2024)
The paper focuses on developing an inventory model for deteriorated item when demand is time- and inventorydependent. Deteriorated items can usually be found in items such as vegetables, fruit, milk, chemical product, pharmaceutical and it needs special attention in managing this kind of inventory. We model the inventory control for these items by a mathematical model involving time- and inventory-dependent demand and considering the backorder policy in handling shortages. The developed model aims to find the optimal time between replenishment and when inventory drops to zero, which minimizes the total inventory cost. The total inventory cost consists of the purchase cost, the order cost, the holding cost, and the shortage cost. Sensitivity analysis is performed to analyse the effect of changing the parameters’ values to the time between replenishment, when inventory drops to zero, the order quantity, and the total inventory cost. The finding shows that changing the parameters’ values of deterioration rate, demand, unit holding cost, unit holding cost and unit shortage cost will have an impact on the time between replenishment, time when inventory drops to zero, order quantity, and inventory cost.